The Italian debate on the role of regulatory models in the framework of the new European directives on air quality. (4th August 2014) - Cirillo, M.C.; Tamponi, M.; Zanini, G.
This paper addresses some topics from the debate in Italy about the role of regulatory models in the management of air quality. It appears that an effective use of dispersion and transformation models cannot take place unless some 'external' (i.e. prejudices against models) as well as 'internal' (i.e. actual deficiencies in model evaluation and use) issues are overcome. Models play an important role as a complement to a monitoring network, and are indispensable tools in the implementation of an air quality management plan: these points should be taken into account in the new European directives on air quality presently under discussion.